Retinoids and pregnancy: an update. (January 2014) - Browne, Hannah; Mason, Gerald; Tang, Thomas
<x xml:space="preserve">Abstract</x> Key content The use and pharmacokinetics of retinoids. The main known teratogenic effects of retinoids are face, skull, cardiovascular, nervous system and thymic abnormalities. The pregnancy prevention programme must be adhered to when initiating retinoid treatment. Effective contraception should be continued for at least one month after cessation of retinoid treatment. Management options of pregnant women with recent retinoid use or exposure in early pregnancy; including involvement of the specialist multidisciplinary team. Learning objectives To understand the risk and in particular teratogenesis associated with exposure to retinoids peri‐conception. To raise awareness of the pregnancy prevention programme. To highlight the management options for women who become pregnant with recent retinoid use or exposure in early pregnancy. Ethical issues Termination of pregnancy with peri‐conceptual exposure to retinoids. Should isotretinoin be used so widely in the childbearing population when we are aware of its teratogenicity?